2006
DOI: 10.1103/physrevlett.96.017403
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Fermion Fluid in High Magnetic Fields: An Infrared Study ofCeRu4Sb12

Abstract: We report a comprehensive infrared magnetospectroscopy study of a CeRu4Sb12 compound revealing quasiparticles with a heavy effective mass m*, with a detailed analysis of optical constants in fields up to 17 T. We find that the applied magnetic field strongly affects the low-energy excitations in the system. In particular, the magnitude of m* approximately = 70 m(b) (m(b) is the quasiparticle band mass) at 10 K is suppressed by as much as 25% at 17 T. This effect is in quantitative agreement with the mean-field… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 16 publications
(36 reference statements)
1
19
0
Order By: Relevance
“…mir / ffiffiffiffiffi ffi T à p (Garner et al, 2000;Degiorgi et al, 2001;Hancock et al, 2004;Hancock et al, 2006;Okamura et al, 2007). From optical and magneto-optical experiments on numerous nonmagnetic systems, Dordevic, Basov, Dilley et al (2001), Dordevic et al (2006) confirmed the scaling relation m à =m b ¼ ðÁ=k B T Ã Þ 2 between the magnitude of m à and the hybridization gap Á.…”
Section: A Heavy-fermion Metalsmentioning
confidence: 79%
“…mir / ffiffiffiffiffi ffi T à p (Garner et al, 2000;Degiorgi et al, 2001;Hancock et al, 2004;Hancock et al, 2006;Okamura et al, 2007). From optical and magneto-optical experiments on numerous nonmagnetic systems, Dordevic, Basov, Dilley et al (2001), Dordevic et al (2006) confirmed the scaling relation m à =m b ¼ ðÁ=k B T Ã Þ 2 between the magnitude of m à and the hybridization gap Á.…”
Section: A Heavy-fermion Metalsmentioning
confidence: 79%
“…Specifically optical studies have provided experimental access to the hybridization strength via direct observation of the hybridization gap ͑⌬͒ in the dissipative part of the optical conductivity ͓ 1 ͔͑͒. [7][8][9][10][11][12][13][14] These studies have also extensively verified the prediction of the PAM on the scaling between the hybridization gap and the effective mass: ͑ ⌬ T Coh ͒ 2 ϰ m * , where T Coh is the temperature below which coherent scattering between magnetic sites emerges. 8 There have also been recent studies of numerous Yb and Ce compounds, that have demonstrated a scaling between the size of ⌬ and T K , the Kondo temperature.…”
Section: Introductionmentioning
confidence: 90%
“…Such a field behavior of the gap has actually been observed for the filled skutterudite CeRu 4 Sb 12 by infrared reflectivity measurements. 62 The La y Fe 4 Sb 12 sample displays strongly different exponents ␣ of 1.61-1.68 ͑in zero field͒ and no shoulder at higher temperatures. With increasing field ␣ tends to slightly higher values but the T 2 law is clearly not achieved for the maximum field.…”
Section: F Electrical Resistivity and Magnetoresistancementioning
confidence: 99%